Microbiome structure in healthy and pregnant women and importance of vaginal dysbiosis in spontaneous abortion - Eslami, Majid; Naderian, Ramtin; Ahmadpour, Ariyan; Shushtari, Ali; Maleki, Sahar; Mohammadian, Parham; Amiri, Arvin; Janbazi, Maryam; Memarian, Mohammad; Yousefi, Bahman (Frontiers in Cellular and Infection Microbiology, 2025)
The vaginal microbiome of healthy women is dominated by Lactobacillus spp. A variety of illnesses, such as vaginosis, sexually transmitted infections (STIs), failed implantation, premature birth (PTB), and preterm pre-labor membrane rupture, are brought on by an unbalanced microbiota. Pregnancy is associated with a decrease in the metabolic capacity of the vaginal resident microbiome, which is consistent with a change to a less complex Lactobacillus-dominated microbiome. Age, race, sexual intercourse, smoking, IUD, contraception, lifestyle, and diet all affect the makeup of the vaginal microbiome. Moreover, physiological events including menarche, the menstrual cycle, pregnancy, menopause, and other hormonal changes have an impact on the vaginal microbiome. The vaginal microbiome is significantly disrupted by the menstrual cycle, with significant changes toward a more varied microbiota occurring around menstruation. Several major factors maintain or disrupt the vaginal microbiome including ethnic group, menstruation cycle, and pregnancy which are discussed in this section. In the index pregnancy, the vaginal microbiota of women who had already given birth, or had just experienced an induced or spontaneous abortion, was qualitatively and quantitatively different from that of women who were having their first child. Early pregnancy vaginal microbiome depletion is a risk factor for early pregnancy miscarriage. Although, early pregnancy miscarriage is not always caused by a high bacterial diversity and quantity of lactobacilli. Lactobacillus protects against pathogens through the production of antibacterial compounds such as lactic acid and bacteriocins.